Immune system defects in DiGeorge syndrome and association with clinical course - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; ÖĞÜLÜR, İSMAİL; BARIŞ, SAFA (WILEY, 2019)
We evaluated 18 DiGeorge syndrome (DGS) patients and aimed to investigate the immunological changes in this population. DGS patients with low naive CD4(+)T and CD8(+)T cells were defined as high-risk (HR) patients, whereas patients with normal numbers of naive CD4(+) and CD8(+)T cells were defined as standard risk (SR) patients. Level of serum IgM, CD3(+) T cell counts and percentages of class-switched memory B cells were significantly low in HR group compared to SR ones. Severe infections and persistent hypoparathyroidism were detected significantly higher in HR group. Patients with reduced percentages of class-switched B cells had earlier onset of infection, lower blood IgM, lower CD4(+) and CD8(+)T counts than patients with normal class-switched memory B cells. Decreased levels of IgM were associated with low numbers of naive CD4(+) and recent thymic emigrants T cells. Monitoring the immune changes of patients with DGS would be useful to predict the severe phenotype of disease.
Keywords: antibodies; immunoglobulins; B cells; DiGeorge syndrome; immunodeficiency; T cells; 22Q11.2 DELETION SYNDROME; REFERENCE VALUES; CHILDREN; AUTOIMMUNITY; PREVALENCE; DEFICIENCY; PHENOTYPE; FEATURES